Comparison of Medical Treatments According to the Characteristics of Idiopathic Premature Ventricular Contractions: Beta-blockers or Calcium Channel Blockers? - Omer Faruk BAYCAN; Serdar FIDAN; Fatma Betul CELIK; Mustafa Adem TATLISU; Serhan OZYILDIRIM; Mustafa CALISKAN (Medeniyet Medical Journal)
Objective: Premature ventricular contractions (PVCs) are a common arrhythmic condition. The first approach in patients with symptomatic and frequent PVC is medical treatment, primarily beta-blockers (BB) or calcium channel blockers (CCB), but it is still unclear which of the two should be chosen. This study investigated which drug treatment would be beneficial according to patient and electrocardiography (ECG) characteristics in patients with idiopathic PVC. Methods: We retrospectively analyzed 156 patients with PVC who came to the cardiology outpatient clinic. Seventy-one patients were responsive to BB, and 85 were responsive to CCB. Their demographic and ECG characteristics were compared. Results: The male ratio was higher (p<0.001), and the left ventricular ejection fraction was lower in BB responders than in CCB responders (p<0.001). Although the mean heart rate was higher in BB responders (p<0.001), the initial PVC burden was lower in BB responders than in CCB responders (p<0.001). The PVC QRS duration was longer in BB responders than in CCB responders (p<0.001). Similarly, the coupling interval variability was higher in BB responders (p=0.006). Conclusions: The evaluation of clinical and ECG parameters in patients with frequent idiopathic PVCs may determine whether BBs or CCBs should be chosen as initial treatment. Further prospective studies are needed to verify our findings and establish their clinical applicability.